YTHDF1 Aggravates the Progression of Cervical Cancer Through m6A-Mediated Up-Regulation of RANBP2 - Wang, Haocheng; Luo, Qingya; Kang, Jianyi; Wei, Qinglv; Yang, Yu; Yang, Dan; Liu, Xiaoyi; Liu, Tao; Yi, Ping (Frontiers in Oncology, 2021)
N6-methyladenosine (m6A) is the most common post-transcriptional modification of RNA in eukaryotes, which has been demonstrated to play important roles in various cancers. YTHDF1 acts as a crucial m6A “reader” and regulates the fate of m6A modified mRNA. However, its role in cervical cancer remains unknown. In this study, we showed that YTHDF1 was highly expressed in cervical cancer, and was closely associated with the poor prognosis of cervical cancer patients. YTHDF1 knockdown suppressed the growth, migration and invasion, and induced apoptosis of cervical cancer cells. Moreover, YTHDF1 knockdown inhibited tumorigenesis of cervical cancer cells in vivo. Through combined on-line data analysis of RIP-seq, meRIP-seq and Ribo-seq upon YTHDF1 knockdown, RANBP2 was identified as the key target of YTHDF1 in cervical cancer cells. YTHDF1 regulated RANBP2 translation in an m6A-dependent manner without effect on its mRNA expression. RANBP2 potentiated the growth, migration and invasion of cervical cancer cells. Our study demonstrated the oncogenic role of YTHDF1 in cervical cancer by regulating RANBP2 expression and YTHDF1 represents a potential target for cervical cancer therapy.